Association between neutrophil percentage-to-albumin ratio and Parkinson’s disease amongst adults in the US - Ke, Li; Tang, Qiaosheng; Li, Ying; Xing, Wenli; Zhao, Lei; Jiang, Sili (Frontiers in Nutrition, 2025)
BackgroundInflammation is an important factor in Parkinson’s disease (PD). Researchers are exploring the integration of multiple biomarkers, including inflammatory and non-inflammatory markers, to enhance predictive value. Neutrophil percentage-to-albumin ratio (NPAR), a novel inflammatory biomarker, offers economic efficiency and accessibility. However, the association between NPAR and PD remains to be elucidated.MethodsWe conducted a cross-sectional study involving participants aged 40 years and above from the National Health and Nutrition Examination Survey (NHANES) database, spanning the years 1999 to 2018. NPAR was calculated as neutrophil percentage (in total white blood cell (WBC) count) (%) × 100/albumin (g/dL). A multivariable logistic regression model was employed to examine the independent association between NPAR and PD while adjusting for demographic factors; educational level; income-to-poverty ratio; smoking status; alcohol consumption; body mass index (BMI); physical activity; and history of hypertension, diabetes, hyperlipidaemia and cardiovascular diseases. Additionally, subgroup analyses were conducted to investigate whether the effect of NPAR varied across different demographic subgroups.ResultsThe NPAR score demonstrates a significant positive correlation with PD. When examined as a categorical variable, individuals in the highest tertiles of NPAR show a 65% increased prevalence of PD compared to those in the lowest tertiles (odds ratio [OR] 1.65 [95% confidence interval CI 1.16, 2.34]). Moreover, weighted restricted cubic spline and threshold effect analyses confirmed a positive association between NPAR and PD, identifying a threshold and saturation effect inflextion point at 9.82. An elevated likelihood of PD development exists beyond the NPAR level of 9.82 (OR 1.12 [95% CI: 1.06, 1.19]). Additionally, subgroup analyses and interaction tests reveal that BMI and hypertension significantly influence the relationship between NPAR and PD (p < 0.05).ConclusionOur study revealed a positive association between NPAR levels and PD, indicating that high NPAR levels are associated with an increased likelihood of developing PD.